India: Akashganga - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Akashganga project launched by the Dairy Cooperative Society (DCS) in Gujarat in 1997, has demonstrated that farmers are open to new technologies, provided they deliver tangible benefits.